The Effect of Massage on Weight Gain in Infants in the Working Area of Puskesmas Kandis - Khairiyah, Fuji Yaumil; Sunarsih, Tri; Jati, Ratih Kumoro (Healthy Tadulako Journal (Jurnal Kesehatan Tadulako), 2025)
Background: Infant weight is a critical indicator of nutritional status and growth. Factors influencing infant weight include breastfeeding frequency and duration. Massage has been identified as a potential intervention to improve infant weight gain. Objective: This study aimed to examine the effect of infant massage on weight gain among infants aged 0 to 12 months in the working area of Puskesmas Kandis. Methods: A quasi-experimental design with a pretest-posttest approach was employed. The population consisted of 33 infants, with 30 infants meeting the inclusion criteria. Primary data were collected through direct observation, while secondary data were obtained from Puskesmas health records. Data were analyzed using the Wilcoxon test in SPSS. Results: The findings showed a significant increase in infant weight after the massage intervention, with a mean weight gain of 0.2977%. Statistical analysis revealed a p-value of 0.000, indicating a significant difference in weight before and after the intervention. A strong correlation was observed between massage and weight gain, with a correlation coefficient of 0.993. Conclusion: Infant massage has a significant positive effect on weight gain. Further research is recommended to explore other factors influencing infant weight gain